CARCINOGENS AND CARCINOGENESIS: MOLECULAR MECHANISMS, RISK FACTORS, AND CONTEMPORARY THERAPEUTIC STRATEGIES FOR MALIGNANT NEOPLASMS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Cancer remains one of the leading causes of morbidity and mortality worldwide. The development of malignant neoplasms results from complex interactions among environmental carcinogens, genetic susceptibility, epigenetic alterations, and dysregulated cellular signaling pathways.
Keywords: Carcinogenesis; Carcinogens; Malignant Neoplasms; Oncogenes; Tumor Suppressor Genes; TP53; DNA Damage; Cell Immortalization; Angiogenesis; Immunotherapy; Targeted Therapy; CAR-T Cell Therapy; Gene Therapy; Nanomedicine.